Perancangan Aplikasi Web E-learning berbasis LMS menggunakan Moodle di PT Global Infotech Solution - Aline Theresia Watania (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
PT Global Infotech Solution is aware of the rapid development of technology nowdays. It takes advantage of every opportunity to widen and expand the creativity of the company’s development. The beneficial cooperation of the health and technology fields is the main topic in making new ideas from bioinformatics technology. With an adequate agency and partnership system, it creates opportunities that can be achieved in making an e-learning web system project. Belajarklikdna is an e-learning website specially made for partners or agents, in facilitating their work by using the moodle platform version 3.9 with an emphasis on the e-learning management system so that this application can be completed and can be used according to the planned targets. It is hoped that through the project of making an e-learning website application, it can make it easy for agency partners who want to broaden their horizon through this application.